Principles of cosmology and gravitation - Berry, Michael (New Delhi, Overseas Press, 2005)
Preface - 1989 reprint, first edition Introduction Cosmography - What the universe contains, The cosmic distance hierarchy and the determination of galactic densities, The red shift and the expansion of the universe Physical basis of general relativity - The need for relativistic ideas and a theory of gravitation, Difficulties with Newtonian mechanics: gravity and inertial frames and absolute space, Inadequacy of special relativity, Mach's principle, and gravitational waves, Einstein's principle of equivalence Curved spacetime and the physical mathematics of general relativity - Particle paths and the separation between events, Geodesics, Curved spaces, Curvature and gravitation General relativity near massive objects - Spacetime near an isolated mass, Around the world with clocks, Precession of the perihelion of Mercury, Deflection of light, Radar echoes from planets, Black holes Cosmic kinematics - Spacetime for the smoothed-out universe, Red shifts and horizons, Apparent luminosity, Galactic densities and the darkness of the night sky Number counts Cosmic dynamics - Gravitation and the cosmic fluid, Histories of model universes The steady state theory, Cosmologies in which the strength of gravity varies In the beginning - Cosmic black-body radiation, Condensation of galaxies, Ylem Appendix - Labelling astronomical objects, Theorema egregium Problems Solutions to odd-numbered problems Useful numbers Bibliography Index
Appendix A-B, 159-163p.; Bibliography 176p.; Index 177-179p.
Keywords: Physics; Cosmology; Gravitation